PENGARUH EKSTRAK DAUN KEMANGI (Ocimum sanctum) TERHADAP KADAR KREATININ TIKUS PUTIH (Rattus norvegicus strain wistar) YANG DIINDUKSI MONOSODIUM GLUTAMATE (MSG) - Sukma Sahreni; Hanny Mindasari; Siti Nurfitri Anugrah Bintani (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Acute Kidney Injury (AKI) is defined as a sudden impairment of kidney function. The main indicator of the severity of AKI is an increase in creatinine levels. One substance that can cause oxidative stress and damage the kidney system is Monosodium glutamate (MSG). MSG at a dose of 4,8g/kgBB was proven to cause damage to the kidneys of mice. Flavonoids found in plants function as natural antioxidants with their ability to ward off free radical molecules. One of these plants is basil leaves (Ocimum sanctum). The aim of this research was to determine the effect of basil leaf extract on creatinine levels in white mice induced by Monosodium glutamate (MSG). Methods: The rats in this study totaled 25, divided into 5 groups: negative control (received aquadest and standard rat feed), positive control (received MSG at 4.8g/kg body weight for 14 days), and three treatment groups (MSG + basil leaf extract at doses of 700 mg/kg body weight, 1,050 mg/kg body weight, and 1,400 mg/kg body weight for 10 days). Data analysis was conducted using One Way Anova followed by Post Hoc Tamhane test. Results: The results of the One Way Anova test on creatinine levels showed that there was an effect after administering basil leaf extract among the five treatment groups, p = 0.000. The results of the Post Hoc Tamhane test showed that basil leaf extract had the activity of inhibiting the formation of creatinine levels which was effective at a dose of 1,050 mg/kgBW p = 0.011. Conclusion: Based on the research results, it can be concluded that basil leaf extract can reduce creatinine levels induced by Monosodium glutamate (MSG). Keywords: Basil Leaf Extract, Creatinine, Monosodium glutamate, Acute Kidney Injury